Management of Facial Nerve Schwannoma: A Multicenter Study of 50 Cases - Eshraghi, Adrien A.; Oker, Natalie; Ocak, Emre; Verillaud, Benjamin; Babcock, Thomas; Camous, Domitille; Kravietz, Adam; Morcos, Jacques; Herman, Philippe; Kania, Romain (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective In the management of facial nerve schwannoma (FNS), surgical tumor resection is now often being replaced with more conservative approaches, such as observation with serial imaging or stereotactic radiosurgery (SRS). Given the scarcity of these lesions, determining the optimal management of FNS remains challenging and subject of debate with multiple treatment approaches supported in the literature.Methods A retrospective chart review was performed in two academic centers for patients diagnosed with FNS between 1996 and 2017. The clinical presentation, treatment modalities employed, tumor control rates, and facial nerve function (FNF) outcomes (House–Brackmann system) were assessed and analyzed.Results The study comprised 50 adult patients. Initial treatment modalities included observation with serial clinicoradiologic review in 27 patients (54%), surgery in 17 patients (34%), and SRS in 6 patients (12%). The FNF were decreased in more than half of the patients who had surgery. Nonetheless, more than 80% of the patients who were initially managed with observation or SRS had stable or improved FNF.Conclusion A prevailing trend toward more conservative treatment modalities for FNS has evolved over time, providing relatively long-term preservation of FNF. As there are multiple management options available, it is of paramount importance that the treating physician be familiar with all treatment modalities and outcomes and counsel patients appropriately. The surgery should be reserved for large tumors and poor FNF at initial presentation or follow-up while watchful observation with imaging is the treatment of choice for rest of the patients.
Keywords: facial nerve schwannoma; outcome; radiosurgery; observation